Analysis of MSMEs Recovery using Digital Technology in the Covid-19 Pandemic Era - Aviza Dwi Amalia; Fadilla Citra Melati (Universitas Muhammadiyah Ponorogo, 2021)
The goal of this study is to examine the MSMEs sector's defense and recovery from the COVID-19 pandemic's slump. Not only is the COVID-19 epidemic wreaking havoc on people's health, but it's also wreaking havoc on the global economy, which has seen a substantial drop. Because the MSMEs sector was formerly a large contributor to Indonesia's Gross Domestic Product, it is one of the sectors most hit by the COVID-19 epidemic. More than half of all MSMEs had previously gone bankrupt and had to close their doors. The drop in product demand resulted in a fall in MSMEs actors revenue turnover, which had an impact on the laid-off workforce. However, in light of the current circumstances and conditions, the government and MSMEs owners are not powerless to find a way out of this downturn. In this epidemic era, the government has partnered with digital e-commerce platforms like as Lazada, Shopee, Bukalapak, Tokopedia, and others to give facilities for MSMEs players to survive and grow their businesses. Furthermore, MSMEs owners take use of the potential of social media to advertise their MSMEs goods, allowing them to continue their company without having to meet with potential customers face to face. Even though the COVID-19 epidemic has not yet finished, this is projected to turn MSMEs into national economic restorers.